Some Pharmacological Observations on Albendazole in Chicks Experimentally Infected with Raillietina tetraqona (Journal of Veterinary Medicine and Animal Production, 2021)
The efficacy of Albendazole against experimental Raillietina tetragona infection in poultry was evaluated in this study. Thirty six, one day-old male Lohmann layer chicks were purchased and reared at the premises of the Faculty of Veterinary Medicine, University of Khartoum. The birds were randomly divided into three groups (twelves birds each group). All birds in each group were experimentally infected with the infective stage of the parasite at a dose rate of three cysticercoids administered orally. Three weeks post-infection, Group 1 was kept as infected untreated control, whereas group 2 and 3 were treated with Albendazole orally at dose rates of 2.5 mg and 25 mg per kg per day for 3-7 days, respectively. Seven days from cessation of Albendazole treatment, all birds in the three groups were slaughtered. Necropsy findings were recorded and blood samples were collected for biochemical analysis. The presented data indicated that oral administration of Albendazole at a dose rate of 25 mg/kg/day for 3-7 successive days provide an effective treatment against this poultry cestodes. The efficacy of the drug was estimated to be 100% as judged by adult worms’ recovery, faecal eggs counts and by comparison of lesions in treated chicks and untreated infected controls. It is recommended that Albendazole should be used as an effective drug for treatment of R. tetraqona infection in susceptible birds.